HUBUNGAN PENGETAHUAN PENDERITA DIABETES MELITUS TERHADAP KEJADIAN LUKA DIABETES MELITUS DI RUANGAN PENYAKIT DALAM RSUD ARIFIN ACHMAD PEKANBARU - Putri Wulandini; Roni Saputra (Jurnal Keperawatan Abdurrab, 2016)
Diabetes mellitus is a heterogeneous group of disorders characterized by increased blood glucose levels, or hyperglycemia. The purpose of this study was to analyze the relationship between knowledge Diabetes Mellitus Diabetes Mellitus on the incidence of injury. The design study is an analytic correlation by using a research instrument a questionnaire and observation sheet. Total population in this study as many as 70 people. Sampling using accidental sampling, scuba 3 weeks, the number of samples in this study 29 respondents. Analyzed using chi-square test. This research is quantitative. The study was conducted at room Disease Arifin Achmad Pekanbaru. The result showed knowledge of Diabetes Mellitus high majority of 15 respondents (51.7%), with the incidence of the majority did not happen 20 respondents (69.0%). (P value 0.02 <0.05 This suggests there is a relationship between knowledge Diabetes Mellitus with injury incidence of diabetes mellitus. It is suggested to patients with diabetes mellitus, in order to always be looking for information on Diabetes Mellitus, efforts to prevent injuries Diabetes Mellitus.